EFFECTIVENESS OF SFBC GROUP COUNSELING WITH EXCEPTION AND MIRACLE QUESTION TECHNIQUES TO INCREASE SELF CONTROL IN STUDENTS AS BRAWLER IN NATIONAL VOCATIONAL SCHOOL AT CIREBON - Widayanti Widayanti; Sugiyo Sugiyo; Ali Murtadho (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The purpose of this study is (1) To analyze the effectiveness of SFBC group counseling with an exception technique in increasing self control of students who fight in the SMK National Cirebon. (2) To analyze the effectiveness of SFBC group counseling with miracle question techniques in improving self control of students who fight in the SMK National Cirebon. The research method uses true experimental method with pretest-post control group design. Data collection techniques using questionnaires, and documentation. Data analysis techniques using descriptive statistics, and inferential statistics with the average difference test.The results of the study concluded that (1) There is effectiveness of SFBC group counseling with exception techniques to improve self-control in group A on the results of hypothesis testing with paired sample test analysis, meaning that SFBC group counseling with exception techniques succeeded in increasing self-control in students fighting at the Cirebon National Vocational School. (2) There is effectiveness of SFBC group counseling with miracle question technique on increasing self-control in group B, on the results of hypothesis testing with Wilcoxon test analysis, meaning that SFBC group counseling with miracle question technique has succeeded in increasing self-control in students fighting in SMK National Cirebon